Price comparison website using web scraping / Nisa Asila Mohd Noor - Mohd Noor, Nisa Asila (2016)
Online shopping is a process in which buy goods or service through the Internet. Nowadays, many online shopping exist in Malaysia such as Lazada.com.my, mudah.my, lelong.my and many more. Since there are too many online shopping website there are still hard to make decision and find the best deals. To overcome this problem, price comparison online shopping website is develop. The purpose of this project for ease the user to online shopping. This project used web scraper to extract each detail of product which are title, image, links, price, and description. Website mudah.my and lazada.com.my are the website to compare the price. User need to enter keyword or name of the item they want and then process extract the detail of item from website mudah,my and lazada.com.my using web scraping then it will combine the output of the process and display the result from both website. A survey has been conducted in order to know opinion from respondent about this project, whether they find this website useful and are they satisfy with this website. Result from a survey shows that respondent find this website is useful and they are satisfy. Therefore, this project might be a help to overcome the problems. For future work, interface can be enhance by classify the item by category.